THE EFFECTIVENESS OF PROJECT-BASED LEARNING IN LANGUAGE EDUCATION - Pirnazarova S.D.; Bagautdinova I.S. (Western European Studies, 2024)
This article is dedicated to investigating the effectiveness of project-based activities in foreign language education. In the context of the modern educational environment, where the focus is on developing communicative skills, project-based activities have become an important component of the learning process. The article explores the theoretical aspects of the project method, analyzes its advantages compared to traditional teaching methods, and presents examples of successful project implementation in various contexts of language learning. Special attention is given to the role of project-based activities in developing language competence, student motivation, and fostering skills in critical thinking and teamwork. The conclusion provides practical recommendations for educators on implementing the project method in the educational process.
Keywords: project-based activities; foreign language education; language competence